Nurse-delivered acupressure on early postoperative gastrointestinal function in patients undergoing colorectal cancer surgery - Yunhong Liu; Carmen W.H. Chan; Ka Ming Chow; Binbin Zhang; Xue Zhang; Chao Wang; Guangzhong Du (Elsevier, 2023)
Objective: Postoperative gastrointestinal dysfunction occurred up to 25% of patients who undergo colorectal cancer surgery, which could cause severe complications and increase economic burden. This study aims to evaluate the effectiveness of nurse-delivered acupressure on early postoperative gastrointestinal function among patients undergoing colorectal cancer surgery. Methods: A total of 112 adult patients (≥ 18 years) scheduled to receive colorectal cancer surgery were randomized into two groups. Acupressure was practiced at ST36 for five days after operation, while the control group used gently rubbing skin. Primary outcomes were the time to first passage of flatus and defecation, while the secondary outcomes were the degree of abdominal distention and bowel motility. The Student's t-test and Mann-Whitney U test or Chi-square test and regression analyses were used, while for repeated measures of outcomes, area under the curve (AUC) was compared between groups and subgroups. Results: After adjusting for potential confounding variables, acupressure significantly shortened the time to have first flatus passage by 11.08 ​h (95% CI: −19.36 to −2.81; P ​< ​0.01). The first passage time of defecation (mean, 77.00 ​± ​36.27 ​h vs. 80.08 ​± ​28.88 ​h), abdominal distention (AUC, 5.68 ​± ​5.24 vs. 5.92 ​± ​4.03), and bowel motility (AUC, 12.09 ​± ​4.70 vs. 11.51 ​± ​3.00) in the intervention group had some improvement although the differences were not statistically significant (P ​> ​0.05). Conclusions: This study indicated that acupressure done by trained nurses could be an effective and feasible solution to promote early gastrointestinal function recovery among patients undergoing colorectal cancer surgery. Trial registration: Chinese Clinical Trial Registry (ChiCTR-IOR-17012460).